Multi-Domain Synergies: Machine Learning, Blockchain, Cloud, IoT, and Big Data in Industry 5.0 - Dr. Smrity Prasad, Azyk Orozonova; Dr. S. Ajit, Dr. M. Paulmurugan; Zamirbekov Uluk, Dr. Lokesh P Gagnani (Journal of Informatics Education and Research, 2025)
Industry 5.0 will play an essential role within bringing the change, shifting between the techno-centric efficiency of Industry 4.0 to a human-centric, resilient, and sustainable one. It is not a product of particular technologies but rather a combination of technologies (Machine Learning (ML), Blockchain, Cloud Computing, the Internet of Things (IoT) and Big Data analytics). To examine such multi-domain synergies, the paper uses a given corpus of research, which serves as its methodology, empirical, secondary based data, in which Usman et al. research is utilized exclusively. As it is shown in the discussion, the combination of these technologies is compounding, which underpins the pillars of Industry 5.0. These outcomes are listed in the manner that shows how IoT and Big Data will form the sensory layer, Cloud will be the lower-level infrastructure, ML will be the intelligence engine to provide strategic decisions, and Blockchain will add a layer of trust and security. This convergence is depicted to support hyper-personalized customer experience, develop streamlined and robust supply chains, and lead to sustainable organizational experiences. The paper ends by concluding that the concepts of technological synergy, as manifested in business and marketing research, can be readily applied and effectively used to create the human-centred, resilient, and sustainable industrial systems projected by Industry 5.0.